Molecular data reveal unexpected species diversity of tapeworms of Australasian reptiles: revision of Kapsulotaenia (Cestoda: Proteocephalidae) - de Chambrier, Alain; Brabec, Jan; Scholz, Tomáš (Zootaxa, 2020)
Species diversity and interrelationships of tapeworms of the genus Kapsulotaenia Freze, 1963 (Proteocephalidae: Acanthotaeniinae), parasites of lizards, especially monitors (Varanus spp.) in the Australasian region, were re-assessed using an interdisciplinary approach. Molecular phylogenetic analyses of newly characterized lsrDNA and cox1 sequences confirmed monophyly of the genus, which is typified by the presence of eggs in capsules, and also indicated a strict (oioxenous) level of host specificity of its species thus revealing unexpected species diversity. Diagnoses of insufficiently described species were amended based on a study of the types and freshly collected specimens and, in addition, three new species were described. A list of ten species of the genus recognized as valid is provided, including illustrations of taxonomically important structures of poorly known taxa. Kapsulotaenia beveridgei n. sp. from V. rosenbergi in Australia differs from all other species of Kapsulotaenia but K. frezei and K. saccifera by having a lower number of testes and an absence of banana-shaped clusters of eggs. Kapsulotaenia cannoni n. sp. from V. gouldii can be distinguished from all species but K. chisholmae by a smaller scolex diameter and from all remaining species by its bigger cirrus-sac ratio and a bigger Mehlis’ gland/proglottid width ratio. Kapsulotaenia cannoni n. sp. differs from K. chisholmae, by the presence of an armed cirrus and a lower number of eggs in cluster (3–7 versus 8–13). Kapsulotaenia nybelini n. sp., which also occurs in V. gouldii, differs from K. tidswelli, K. frezei and K. beveridgei by having a greater number of testes, and it differs from K. varia by having a smaller relative size of the ovary. It differs from K. saccifera by the absence of banana-shaped cluster, and from K. pythonis by the number of eggs in clusters. Identification keys for all species of Kapsulotaenia and genera of the Acanthotaeniinae are also provided, together with SEM micrographs of three species, including two newly described species.